Прогнозирование функциональных свойств имплантов с эффектом памяти формы с использованием компьютерного моделирования - Бокиев, Тимур Парвизович (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The functionality of implants made of titanium nickelide for spinal surgery have been studied. The main feature of titanium nickelide used in their production is the manifestation of the shape memory effect under thermomechanical influences. It is on this effect that their technological behavior during implantation is based. The use of numerical simulation in the process of designing medical devices makes it possible to avoid many errors and repeated medical interventions. In the work, the conditions for installing spinal implants in the intervertebral region during surgical intervention were simulated by numerical simulation methods. The selected physical and mathematical model in the continuum approximation takes into account the features of direct and reverse phase transitions in the material under the influence of temperature, which allows specialists to make a prediction about the functionality of products, choose an acceptable size depending on the conditions of use during implantation. The developed modeling algorithm is applicable to a wide class of products united by a single principle of using the shape memory effect.